2002
DOI: 10.1073/pnas.202608199
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the host response to hepatitis C virus infection

Abstract: We have examined the progression of hepatitis C virus (HCV) infections by gene expression analysis of liver biopsies in acutely infected chimpanzees that developed persistent infection, transient viral clearance, or sustained clearance. Both common responses and outcome-specific changes in expression were observed. All chimpanzees showed gene expression patterns consistent with an IFN-␣ response that correlated with the magnitude and duration of infection. Transient and sustained viral clearance were uniquely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
235
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 798 publications
(262 citation statements)
references
References 72 publications
20
235
0
2
Order By: Relevance
“…Inhibition of fatty acid synthesis by inhibiting acetyl-CoA carboxylase led to a decrease in HCV replication, consistent with our previously published data (12), which demonstrated that inhibition of FAS by using the drug cerulenin inhibited replication of the subgenomic HCV RNA replicon. We have further demonstrated that saturated and monounsaturated fatty acids can enhance HCV RNA replication, consistent with the requirement of the fatty-acid-biosynthetic pathway in HCV RNA replication.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Inhibition of fatty acid synthesis by inhibiting acetyl-CoA carboxylase led to a decrease in HCV replication, consistent with our previously published data (12), which demonstrated that inhibition of FAS by using the drug cerulenin inhibited replication of the subgenomic HCV RNA replicon. We have further demonstrated that saturated and monounsaturated fatty acids can enhance HCV RNA replication, consistent with the requirement of the fatty-acid-biosynthetic pathway in HCV RNA replication.…”
Section: Discussionsupporting
confidence: 92%
“…1). These data, along with previous gene-expression profiling analyses in acutely infected chimpanzees (12), suggest that HCV may directly or indirectly induce cholesterol and͞or fatty-acidbiosynthetic gene expression.…”
Section: Generation Of Ribonuclease-protection Assay (Rpa) Probes Forsupporting
confidence: 65%
See 1 more Smart Citation
“…Recent reports suggest that lipid biosynthesis affects HCV replication (7)(8)(9). Involvement of a geranylgeranylated host protein, FBL2, in HCV replication through the interaction with NS5A suggests that the cholesterol biosynthesis pathway is also important for HCV replication (9).…”
mentioning
confidence: 99%
“…Biosynthesis of cholesterol is regulated by SREBP-2, whereas that of fatty acids, triglycerides, and phospholipids is regulated by SREBP-1c (10)(11)(12)(13)(14). In chimpanzees, host genes involved in SREBP signaling are induced during the early stages of HCV infection (8). SREBP-1c regulates the transcription of acetylCoA carboxylase, fatty acid synthase, and stearoyl-CoA desaturase, leading to the production of saturated and monounsaturated fatty acids and triglycerides (15).…”
mentioning
confidence: 99%